Cornelis De Bie, il Gulden Cabinet e la pittura di natura morta e di genere in Italia - Fiorentino, Luca (Venezia Arti, 2020)
This article spotlights the lives of Italian still life painters in one of the most important seventeenth-century Flemish source texts: Het Gulden Cabinet van de edel vry schilder-const by Cornelius De Bie (1662). This essay offers the first Italian translations of texts dedicated to these painters and examines the intrinsic motivations that led De Bie to choose them as the subject of his panegyrics. The writing underscores the connections De Bie must have had with information brought home by his father (who lived in Rome for years), with Gaspar Roomer and his collections, and with Italian art literature, to which he owed a debt as for information obtained and source documents. In addition, the article discusses the life of Pieter Boel, who spent many years in Italy, and of one of his best pupils, David De Coninck.